Effect of Sexual Counseling on Stress, Anxiety, and Depression in Women during Postpartum Period - maryam zamani; Robab Latifnejad Roudsari; Maryam Moradi; Habibollah Esmaily (Mashhad University of Medical Sciences, 2017)
Background: Sexual dysfunction can lead to anxiety and depression. Failure to have sexual counseling during postpartum period is one of the issues that could affect sexual dysfunction within this period. Aim: This study aimed to investigate the effect of sexual counseling on stress, anxiety, and depression in women during postpartum period. Method: This single-blind randomized clinical trial was conducted on 75 postpartum women within the age range of 18-35 years, referring to four health centers of Mashhad, Iran, in 2016. The data were collected using the Depression Anxiety Stress Scales-21. The intervention included four 60 to 90-minute sessions of sexual counseling, performed within eight weeks. The control group received the routine care. The questionnaires were completed eight weeks after the end of the intervention. The data were analyzed by SPSS version 16 using the independent t-test and Mann-Whitney U test. Results: The mean ages of the participants were 29.5±4.3 and 29.4±4.2 years in the intervention and control groups, respectively. The results of the Independent t-test, showed the mean stress score was significantly lower in intervention group (P = 0.04) and Mann-Whitney test, showed a significant decrease in the mean anxiety (P=0.01) and depression (P=0.003) scores, in intervention group compared to the control group 8 weeks after the intervention. Implications for Practice: Sexual counseling can be helpful to decrease stress, anxiety, and depression in the women suffering from sexual problems during postpartum period.